The Sustainability of Agro-Food and Natural Resource Systems in the Mediterranean Basin 2015
DOI: 10.1007/978-3-319-16357-4_14
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife Agriculture Interactions, Spatial Analysis and Trade-Off Between Environmental Sustainability and Risk of Economic Damage

Abstract: Over the last few years, wildlife damages to the agricultural sector have shown an increasing trend at the global scale. Fragile rural areas are more likely to suffer because marginal lands, which have little potential for profit, are being increasingly abandoned. Moreover, public administrations have difficulties to meet the growing requests for crop damage compensations. There is therefore a need to identify appropriate measures to control this growing trend. The specific aim of this research is to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…In fact, the requests for crop damage compensations are becoming more and more difficult to be met by public administrations, and this in turn generates conflicts between farmers, managers of protected areas, and hunters. A deep knowledge of the phenomenon and of the relative risks and the identification of cost-effectiveness parameters are therefore highly required, in order to ensure greater effectiveness of public actions (Cozzi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the requests for crop damage compensations are becoming more and more difficult to be met by public administrations, and this in turn generates conflicts between farmers, managers of protected areas, and hunters. A deep knowledge of the phenomenon and of the relative risks and the identification of cost-effectiveness parameters are therefore highly required, in order to ensure greater effectiveness of public actions (Cozzi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for a more exhaustive analysis, the impact of other variables related to the dependent variable should be tested, especially for areas with lower R 2 that indicate the need for additional covariates. For example, further studies could focus on the number of hunters, factors related to seasonality (the nutrition needs of different ungulate species vary in summer compared to in winter), different vegetation cover or types of forestry (Côté et al 2004;Cozzi et al 2015;Gill and Beardall 2001;Jensen et al 2014;Horsley et al 2003;Trdan and Vidrih 2008;Allen et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have reviewed and estimated the economic impacts of ungulates (see, among others, Gill 1992;Gill and Beardall 2001;Horsley et al 2003;Apollonio et al 2011). In a south region of Italy (Basilicata) Cozzi et al (2015) observed that between 2007 and 2012, the surface areas damaged by ungulates increased from 2800 to 5850 ha and as consequence the estimated compensations increased significantly from €550,000 up to €1,134,000. In North America, the US Department of Agriculture Wildlife Service (USDA 2012) reported in 2009 that the damage to agriculture, mainly due to the presence of wild boar and deer, was estimated at about $71,000,000, mostly from lost revenue.…”
Section: Introductionmentioning
confidence: 99%
“…Dzik zaliczany jest do zwierząt wolnożyjących, charakteryzujących się najbardziej efektywną rozrodczością (2). Przyjmuje się, że średnioroczny przyrost populacji dzika w Europie wynosi około 100%.…”
Section: Struktura Populacji Dzikówunclassified